Presença de Imidacloprid e Fipronil no mel e o efeito em operárias de Apis mellifera L. (Hymenoptera: Apidae) africanizada - Paloschi, Cristiane Lurdes (2021)
Synthetic phytosanitary products are indicated as one of the main factors that cause population decline in Africanized Apis mellifera honeybee colonies, affecting their survival and contaminating their sub products, such as honey. Therefore, the objective of this research was to evaluate the toxicity levels that the insecticides imidacloprid and fipronil, used in the soybean production chain, generate orally, topically and by contact in worker bees of Africanized A. mellifera, besides verifying whether these active ingredients could be found in honey samples. The toxicity levels were verified by bioassays. In bioassays 1 the levels correspond to the percentages of 100, 10, 1, 0.1 and 0.01% of the recommended concentration of application of the commercial products Nortox® (active ingredient imidacloprid) and NortoxWG® (active ingredient fipronil) in the field. Thus, the average lethal concentrations (LC50) were obtained in 48 hours for A. mellifera, by contact on contaminated surface, which led to the determination of the ranges of concentration levels to be used for the next bioassays. Bioassays 2 and 3 followed the guidelines of the Organisation for Economic Co-operation and Development (OECD, guide no. 213 and no. 214 of 1998), determining the LC50 (48 hours) of the insecticides imidacloprid and fipronil, for A. mellifera topically and orally. In bioassay 4, LC50 (48 hours) and bee survival rate for a period of 120 hours were determined through surface contact contaminated by the insecticides imidacloprid and fipronil and their interference in honeybee behavior. Honey samples were collected in agroecological and conventional georeferenced apiaries. The traces of the insecticides imidacloprid and fipronil in the samples were detected by high-pressure liquid chromatography (HPLC-UV) and gas chromatograph-electron capture detector (GC-ECD) with extraction by SPE C18. It was verified that the survival of honeybees was directly affected in relation to the concentration used and exposure time, as well as their behavioral capacity, demonstrating the negative residual effect that imidacloprid and fipronil have on the workers of this species. Honey samples from conventional apiaries displayed detection of imidacloprid and fipronil insecticides above the maximum residue limits (MRL) allowed by the European Union (0.05 μg mL-1) and samples from agroecological apiaries did not show traces of these products. The insecticides imidacloprid and fipronil affect the survival rate and behavioral capacity of Africanized A. mellifera, as well as the quality of honey.